Application of the Listening Learning Model with Strategy Bottom Up and Top Down - Yusuf, Rusydi Muhammad (JUPE : Jurnal Pendidikan Mandala, 2023)
Listening is a very important language skills, because listening is a receptive skill. Someone who can listen well will gain knowledge easily. A student who has good skill in listening will be able to express their opinions well. The purpose of this research is to improve students' ability in listening comprehension ranging from the simple to the difficult to understand. This research is a Classroom Action Research by using Bottom-up and Top-down strategies applied simultaneously. This research was conducted at University of Darma Persada Jakarta, the object of the research are the students of English Language and Culture Department. Based on results of this Classroom Action Research that Bottom Up strategy has to be applied earlier than Top Down Strategy, because to be able to listen well to be started from how to pronounce of the word , understand simple paragraphs leads to the more difficult and complicated paragraphs to understand.